Structural and morphological characteristics of the zone of hybridization under different moisture of the dentin of the caries cavities. - Samoilenko, A. V.; Pomoynitskaya, M. V. (Морфологія / Morphologia / Morfologìâ, 2012)
The aim of the study was to investigate the hermetic seal of fit and ultrastructure of the hybrid layer using adhesive systems with different solvents. At 108 extracted teeth examined quality of fit of the seal and microstructure of interaction of adhesive and hard tissues of the tooth dentin with varying humidity and, depending on the type of solvent adhesive systems. Found that the need for a differentiated approach to the choice of the parameter humidity dentin cavity at a choice of different adhesive systems. And evaluation of regional penetration of the dye on the boundary of the "tooth-filling" and the study of the architectonics of adhesive bonds at the microstructural level, showed that 19.7% of the most moisture is indicated for use of adhesive systems with an aqueous solvent, 20.0% - from ethanol and 20.3% - with acetone solvent. Derivations approach to dentin moisture creates optimal conditions for inside of the dentin adhesive penetration and the formation of hermeticism, which further improves the durability of the functioning of the seal.